Apocalyptic bodies : the biblical end of the world in text and image - Pippin, Tina, 1956- (Routledge, 1999)
Apocalyptic Bodies traces the biblical notions of the end of the world as represented in ancient and modern texts, art, music and popular culture, for example the paintings of Bosch. Tina Pippin addresses the question of how far we, in the late twentieth century, are capable of reading and responding to the 'signs of the times'. It will appeal not only to those studying religion, but also to those fascinated with interpretations of the end of the world.
Keywords: Apocalyptic literature.; End of the world -- Biblical teaching.; End of the world in literature.; End of the world in art.; Apocalypse in literature.; Apocalypse in art.; Littérature apocalyptique.; Fin du monde -- Enseignement biblique.; Fin du monde dans la littérature.; Fin du monde dans l'art.; BIBLES -- General.; RELIGION -- Biblical Reference -- General.; RELIGION -- Biblical Reference.; Apocalypse in literature; Apocalypse in art; Apocalyptic literature; End of the world -- Biblical teaching; End of the world in art; End of the world in literature